Acute severe myocarditis with cardiac thrombus formation ─ A therapeutic challenge - Pereira,Isabel Ayres (2022)
Abstract Acute myocarditis is a potentially life-threatening disease in pediatric age, with risk of severe cardiac dysfunction and intracardiac thrombus formation. A previously healthy 16-year-old boy was admitted to the Pediatric Intensive Care Unit with suspicion of acute myocarditis with multiorgan dysfunction. He reported mucous diarrhea, vomiting, and asthenia with one week of evolution. The echocardiogram revealed moderate-to-severe left ventricle dysfunction with mitral and tricuspid regurgitation and two hyperechoic images suggestive of thrombus, later confirmed by cardiac magnetic resonance. Unfractionated heparin was started on admission. Campylobacter jejuni was isolated from feces. Despite treatment, the clinical picture worsened with systemic arterial embolization. Surgical thrombectomy was performed on day 13, and extracorporeal membrane oxygenation (ECMO) was maintained until day 28. At this time, the boy was submitted to orthotopic cardiac transplantation with favorable postoperative course. The therapeutic approach in these cases is controversial and should always be multifactorial and multidisciplinary. Despite the inherent risk of complications, thrombectomy should be considered when conservative approaches fail.